Factors Influencing Relapse After Omalizumab in Chronic Urticaria. Does the Method of Discontinuation Influence Relapse? - Üstün, Petek; Adışen, Esra (Dermatology Practical & Conceptual, 2025)
Introduction: Omalizumab is recommended until spontaneous remission occurs rather than for a specific period of time in chronic urticaria (CU). The rate of recurrence of symptoms after treatment varies depending on the method of discontinuation. Objectives: Our study aimed to investigate how the method of omalizumab discontinuation, as well as other factors, affects the rate of post-treatment relapses. Methods: Patients with CU were divided into 3 groups based on their method of discontinuing omalizumab treatment: direct discontinuation, extending treatment intervals to 8 weeks, and reducing the treatment dose to 150 mg/4 weeks. These groups were then compared for relapse rates. Results: A total of 200 patients were included in this study. Among the 109 patients who discontinued omalizumab directly, 65.1% experienced a relapse. The relapse rate was 40.7% in those who extended the treatment interval to 8 weeks, and 15.6% in those who reduced the dose to 150 mg/4 weeks. There was a statistically significant difference in post-treatment relapse rates according to the method of discontinuation (p < 0.001). Conclusions: Gradual tapering of treatment rather than direct discontinuation has been shown to prolong remission. Achieving the lowest relapse rate with a reduction of the treatment dose to 150 mg/4 weeks is significant for the design of omalizumab discontinuation protocol and provides insight for future studies.